Central-Bank Independence, Economic Behavior, and Optimal Term Lengths - Waller, Christopher J.; Walsh, Carl E. (American Economic Review, 1996)
We parameterize central-bank independence in terms of partisanship and term length, and we focus on the implications of alternative policy structures for real economic activity. While long terms of office for the central banker can reduce the role of electoral surprises, term lengths that are too long are costly if societal preferences are subject to permanent shifts. The appointment of a conservative central banker increases the optimal term length and leads to lower average inflation but need not increase the volatility of output.